Dietary antioxidants, lipid peroxidation and plumage colouration in nestling blue tits Cyanistes caeruleus. - Larcombe, S; Mullen, W; Alexander, L; Arnold, K (2010)
Carotenoid pigments are responsible for many of the red, yellow and orange plumage and integument traits seen in birds. One idea suggests that since carotenoids can act as antioxidants, carotenoid-mediated colouration may reveal an individual's ability to resist oxidative damage. In fact, there is currently very little information on the effects of most dietary-acquired antioxidants on oxidative stress in wild birds. Here, we assessed the impacts on oxidative damage, plasma antioxidants, growth and plumage colouration after supplementing nestling blue tits Cyanistes caeruleus with one of three diets; control, carotenoid treatment or α-tocopherol treatment. Oxidative damage was assessed by HPLC analysis of plasma levels of malondialdehyde (MDA), a by-product of lipid peroxidation. Contrary to predictions, we found no differences in oxidative damage, plumage colouration or growth rate between treatment groups. Although plasma lutein concentrations were significantly raised in carotenoid-fed chicks, α-tocopherol treatment had no effect on concentrations of plasma α-tocopherol compared with controls. Interestingly, we found that faster growing chicks had higher levels of oxidative damage than slower growing birds, independent of treatment, body mass and condition at fledging. Moreover, the chromatic signal of the chest plumage of birds was positively correlated with levels of MDA but not plasma antioxidant concentrations: more colourful nestlings had higher oxidative damage than less colourful individuals. Thus, increased carotenoid-mediated plumage does not reveal resistance to oxidative damage for nestling blue tits, but may indicate costs paid, in terms of oxidative damage. Our results indicate that the trade-offs between competing physiological systems for dietary antioxidants are likely to be complex in rapidly developing birds. Moreover, interpreting the biological relevance of different biomarkers of antioxidant status represents a challenge for evolutionary ecology.